APLIKASI SISTEM INFORMASI WEB DESIGN PARIWISATA ACEH DAN JASA PENGINAPAN BERBASIS GIS (GEOGRAPHIC INFORMATION SISTEM) - mutammimul Ula; Ar Razi Ar Razi; Desvina Yulisda; Muhammad Fauzan (LPPM Universitas Al Muslim, 2022)
The purpose of this service is to provide understanding and training of web applications for students to be able to implement web applications into tourism applications. Furthermore, to search for accommodation locations, there are directions for walking using GIS. Furthermore, the GIS application is implemented for locating services on mobile devices and can be accessed via web and mobile networks. The problem with this service is that students do not understand how to make web-based tourism destination applications that produce Location Based Service on web devices and then help to find information and tourism locations from the user's starting point location to the route that can be taken to the tourism location. Furthermore, the use of web media as a medium to find hotel information combined using a web-based mobile application which is a Location Based Service (LBS) according to the user's location to get the location and route to the destination hotel location quickly and easily. The results of this service are students can understand how to make web in applying the web by searching for tourism places by having several main views, namely finding the location of the closest tourism place according to the user's location. Thus this system will make it easier for users or the public to see tourism locations and help the Aceh Culture and Tourism Office in increasing the number of tourism visitors so that it can indirectly increase regional income, especially in the Aceh area.